The Labor movement in Egypt1936-1952Historical study (Journal of the College of Basic Education, 2022)
This stu Keywords. A movement ,struggle, right dy sheds light on the history of the labor movement in Egypt, which was one of the oldest labor movements in the Arab region, which was able to win the rights of the working class by leading strikes in order to demand the legitimate rights of workers and was an example to follow in patriotism, which later became the main driver For the Arab labor movements, the study starts from 1936, the year in which Egypt concluded a friendship treaty with Britain. Instead of improving working conditions in Egypt, the reality was otherwise. The treaty tied Egypt with political and military restrictions that negatively impacted the conditions of the working class in Egypt and pushed To reject and denounce it through Leading strikes and clashes with the British occupiers, and this situation continued until the end of World War II in 1945, when successive Egyptian governments succumbed to the demands of the workers by allowing them to establish trade unions independent of the decisions of the authority. July 1952.